The insertion of two amino acids into a transcriptional inducer converts it into a galactokinase - Platt, Adam (The National Academy of Sciences, 2000)
The transcriptional induction of the GAL genes of Saccharomyces cerevisiae occurs when galactose and ATP interact with Gal3p. This protein-small molecule complex associates with Gal80p to relieve its inhibitory effect on the transcriptional activator Gal4p. Gal3p shares a high degree of sequence homology to galactokinase, Gal1p, but does not itself possess galactokinase activity. By constructing chimeric proteins in which regions of the GAL1 gene are inserted into the GAL3 coding sequence, we have been able to impart galactokinase activity upon Gal3p as judged in vivo and in vitro. Remarkably, the insertion of just two amino acids from Gal1p into the corresponding region of Gal3p confers galactokinase activity onto the resultant protein. The chimeric protein, termed Gal3p+SA, retains its ability to efficiently induce the GAL genes. Kinetic analysis of Gal3p+SA reveals that the K(m) for galactose is similar to that of Gal1p, but the K(m) for ATP is increased. The chimeric enzyme was found to have a decreased turnover number in comparison to Gal1p. These results are discussed in terms of both the mechanism of galactokinase function and that of transcriptional induction.